The effect of ulipristal acetate treatment on symptomatic uterine fibroids within 12-months follow-up - Woźniak, Sławomir; Szkodziak, Piotr; Czuczwar, Piotr; Woźniakowska, Ewa; Paszkowski, Maciej; Milart, Paweł; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2014)
Aim of the study: The purpose of the study was to monitor the effect of ulipristal acetate treatment on symptomatic uterine fibroids within 12-months follow-up. Material and methods : Fifty six patients with symptomatic uterine fibroids qualified for surgical treatment were included in the prospective observational study. All patients received preoperative oral UPA treatment for 3 months (1 × 5 mg). Patients that refused surgical treatment after UPA therapy were followed-up for the next 9 months. The volume of the intramural fibroid was estimated by TV-US using and integrated VOCAL 3D imaging program at baseline, after 3 months of UPA treatment and further at 3-months intervals. Results: Before UPA mean dominant fibroid volume was estimated to be 216.0 cm3 (38.4-768.2 cm 3 ) and decreased to 117.6 cm 3 (12.6-668.0 cm 3 ) after 3 months of UPA therapy. Mean percentage volume reduction was 45.6%. Mean hemoglobin level increased from an initial 10.1 g/dL (6.8-12.9 g/dL) to 12.6 g/dL (10.1-14.8) after 3 months of UPA therapy. At 12 months after initiating UPA treatment mean dominant fibroid volume decreased by 43.9%. In one third of followed-up patients the effect of 3 month UPA therapy persisted for the next 9 months. Conclusions : Three month UPA therapy decreases fibroid volume and improves hemoglobin level before planned surgical treatment. In one third of followed-up patients the effect of 3 month UPA therapy persisted for the next 9 months.